Teaching during the time of COVID: Learning from mentor teachers' experiences. Issue 4 (10th December 2021) - Gawronski, Jenny H.
Abstract: Across the globe, the COVID-19 pandemic has drastically altered the educational landscape, creating new professional realities for practicing and future teachers. As teacher educators prepare preservice teachers for the uncertainty of online and in-person teaching, more information is needed around how mentor teachers designed and implemented their emergency online lessons at the beginning of the pandemic. This study explores the topic by analyzing data from 31 mentor teachers surveyed about their teaching experiences between March and June 2020. The findings suggest that most of the mentor teachers defined similar priorities for creating equitable access to their instructional materials. Accordingly, the mentor teachers focused on increasing their students' access to digital content, designing instruction that considered families' capacity for support, and encouraging student engagement in online learning. These findings have implications for how teacher educators learn from mentor teachers' experiences during this unprecedented period, and work to prepare preservice teachers for the challenges and complexities of online teaching—ultimately helping them develop the skills to adapt to future, unfamiliar teaching environments.